Treatment of melasma in men with low-fluence Q-Switched neodymium-doped yttrium-aluminum-garnet laser versus combined laser and glycolic acid peeling - Vasanop Vachiramon (2018)
© 2015 by the American Society for Dermatologic Surgery, Inc. BACKGROUND Low-fluence Q-switched neodymium-doped yttrium-aluminum-garnet 1,064-nm laser (LFQS) and glycolic acid (GA) peeling have been reported as a treatment option for melasma. However, there are limited data on their efficacy in men. OBJECTIVE To compare the efficacy and safety of LFQS monotherapy with combined LFQS and 30% GA peeling in male patients with melasma. MATERIALS AND METHODS Fifteen males with mixed type melasma were randomized to receive 5 weekly sessions of LFQS on one side of the face and LFQS plus 30% GA peeling on the contralateral side and were followed for 12 weeks. Twelve patients completed the protocol. RESULTS Mean relative lightness index (RL∗I) of the combined treatment side was lowered throughout the study period, with the maximal improvement of 52.3% reduction at the fourth week follow-up (p = .023). Patient selfassessment was favorable in the combined treatment. However, the mean RL∗I increased at 8 and 12 weeks of follow-up. One subject (8.3%) developed guttate hypopigmentation, which did not resolve by the 12-week follow-up. CONCLUSION Low-fluence Q-switched neodymium-doped yttrium-aluminum-garnet 1,064-nm laser combined with GA peeling temporarily reduced melasma in men, but the incidence of side effects does not justify the short-lived benefits of this procedure. This technique requires further study.